2020
DOI: 10.3897/herpetozoa.33.e47279
|View full text |Cite
|
Sign up to set email alerts
|

Shot the spots: A reliable field method for individual identification of Amolops formosus (Anura, Ranidae)

Abstract: Natural body patterns in amphibians are widely used for individual recognition. In this study, we photographed individuals of Amolops formosus for four days of sampling without handling them. We processed 301 photographs of dorsal blotch pattern in HotSpotter software and verified them visually for confirmation. We identified 160 unique individuals of A. formosus based on the images taken in the field, resulting in an abundance estimate of 180 individuals. The success rate in identifying individuals of A. form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This study is one of the first comparing between two commonly used photo-matching algorithms to monitor reintroduced pool frog populations. Our results are comparable to similar studies with sample sizes ranging from 92 to 852 (Elgue et al, 2014;Sannolo et al, 2016;Treilibs et al, 2016;Gonzalez-Ramos,et al, 2017;Navarro et al, 2018;Patel & Das, 2020). Unlike other studies, we applied minimal operator effort (considering only the first potential matches presented as correct or not and only selecting the minimum requirement of 12 feature points when using I3S-Spot) to achieve our findings whereas others used greater levels of user effort (Sannolo et al, 2016;Treilibs et al, 2016;Matthé et al, 2017).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This study is one of the first comparing between two commonly used photo-matching algorithms to monitor reintroduced pool frog populations. Our results are comparable to similar studies with sample sizes ranging from 92 to 852 (Elgue et al, 2014;Sannolo et al, 2016;Treilibs et al, 2016;Gonzalez-Ramos,et al, 2017;Navarro et al, 2018;Patel & Das, 2020). Unlike other studies, we applied minimal operator effort (considering only the first potential matches presented as correct or not and only selecting the minimum requirement of 12 feature points when using I3S-Spot) to achieve our findings whereas others used greater levels of user effort (Sannolo et al, 2016;Treilibs et al, 2016;Matthé et al, 2017).…”
supporting
confidence: 91%
“…There are now several automated software algorithms available that can aid this process and have been employed across a range of taxa, including amphibians (Elgue et al, 2014;Sannolo et al, 2016;Matthé et al, 2017;Speybroeck & Steenhoudt, 2017;Patel & Das, 2020), reptiles (Treilibs et al, 2016), large terrestrial mammals such as the Thornicroft's giraffe (Giraffa cameleopardalis thornicroft) (Halloran et al, 2014) and several species of elasmobranch (Gonzalez-Ramos et al, 2017;Navarro et al, 2018). However, such algorithms require varying amounts of input by the user and image quality (Yoshizaki et al, 2009;Halloran et al, 2014;Urian et al, 2015;Treilibs et al, 2016;Gonzalez-Ramos et al, 2017;Matthé et al, 2017;Gatto et al, 2018), data-set parameters (Matthé et al, 2017), morphological features of the study species (Yoshizaki et al, 2009;Urian et al, 2015;Matthé et al, 2017) and performance rates differ between software types.…”
mentioning
confidence: 99%
“…Recently, it has been shown that HotSpotter can be used for identification of animals that were photographed from the distance (26). Therefore, apart from the general use in traditional population analyses, matching individuals from photos could also be used in citizen science projects.…”
Section: Discussionmentioning
confidence: 99%
“…2G & 2H) demonstrating that ontogenetic changes in colouration and markings are observable in this species. More work would be necessary to determine the extent of individual ontogenetic change, and at which point (if at all) adult colour pattern stabilises to assess the usefulness ofPatel & Das's (2020) technique for long term studies (over months or years).…”
mentioning
confidence: 99%